2019
DOI: 10.18332/tid/106117
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tobacco smoking and dental caries: A systematic review and meta-analysis

Abstract: INTRODUCTION Tobacco is responsible for infaust oral conditions and many oral diseases. Dental caries is one of the most prevalent oral diseases. The association between tobacco smoking and dental caries has become an important recent topic of research. A systematic review and meta-analysis was conducted to evaluate the association between tobacco smoking and dental caries. METHODS A literature search was conducted in the databases PubMed, EMBASE, Medline and Cochrane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…After performing subgroup analysis, adults who were currently smoking and those with lower “family PIR” were more likely to have dental caries. In 2019, a meta‐analysis by Jiang et al suggested that smoking was a risk factor of dental caries (Jiang, Jiang, Wang, & Huang, 2019). In the same line, Chinellato et al., (2018) reported that lower levels of 25(OH)D were associated with passive smoking exposure.…”
Section: Discussionmentioning
confidence: 99%
“…After performing subgroup analysis, adults who were currently smoking and those with lower “family PIR” were more likely to have dental caries. In 2019, a meta‐analysis by Jiang et al suggested that smoking was a risk factor of dental caries (Jiang, Jiang, Wang, & Huang, 2019). In the same line, Chinellato et al., (2018) reported that lower levels of 25(OH)D were associated with passive smoking exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A review of clinical cases of oral diseases managed in dental settings revealed that patients with a history of tobacco use had poorer health outcomes than patients that were non-users of tobacco [5][6][7] . A very effective way to stem the development of tobacco-associated oral diseases is through tobacco cessation interventions 3 .…”
Section: Commentarymentioning
confidence: 99%
“…The Cohen's Kappa index was greater than 0.9 since 2009. iate analysis. [31][32][33][34][35] We constructed the directed acyclic graph (Figure 1). 36 To investigate the association between household food insecurity and the prevalence of untreated dental caries, we used a modified Poisson approach.…”
Section: Assessment Of Dental Cariesmentioning
confidence: 99%
“…According to the United States Department of Agriculture report, 31.6% of low-income households were food-insecure, compared to the national average of 12.3%. 45 Epidemiological studies have shown that oral health outcomes, including dental caries and periodontal diseases, are related to socioeconomic factors.…”
Section: Ta B L Ementioning
confidence: 99%